Penerapan Algoritma K-Medoids Untuk Pengelompokan Data Penerima Bantuan Uang Kuliah Tunggal Bagi Mahasiswa Terdampak Covid-19 - Andrea, Reza; Nursobah, Nursobah (Building of Informatics, Technology and Science (BITS), 2022)
The ongoing Covid-19 pandemic period greatly affects various aspects of life, one of which is the issue of the economy. This problem has an impact on the field of education, one of which is at the university level. where many students whose parents/insurers of tuition fees are experiencing financial constraints due to the impact of the Covid-19 pandemic. So we need an effective way as a recommendation in analyzing student data based on the socioeconomic status of each student's parents in determining the group of UKT recipients. There are many ways that can be used, one of which is by utilizing data mining to group data for students who are entitled to get UKT using the K-Medoids method. The application of the K-Medoids method is used to group data on students who are eligible to receive UKT assistance funds with the aim of being a recommendation in analyzing student data based on the socioeconomic status of each student's parents in determining the UKT recipient group for the university. Whatever the results of the application of the K-medoids method, a group that deserves to be recommended is based on the results of Cluster / Grouping 0 with a total student data of 8 people based on the results of consideration of the criteria used, namely Parents' Occupation, Home Ownership Status and Parents' Income